2011
DOI: 10.1021/ja207971h
|View full text |Cite
|
Sign up to set email alerts
|

Syntheses and Structural Characterizations of Anionic Borane-Capped Ammonia Borane Oligomers: Evidence for Ammonia Borane H2 Release via a Base-Promoted Anionic Dehydropolymerization Mechanism

Abstract: Studies of the activating effect of Verkade's base, 2,8,9-triisobutyl-2,5,8,9-tetraaza-1-phosphabicyclo[3.3.3]undecane (VB), on the rate and extent of H(2) release from ammonia borane (AB) have led to the syntheses and structural characterizations of three anionic aminoborane chain-growth products that provide direct support for anionic dehydropolymerization mechanistic steps in the initial stages of base-promoted AB H(2) release reactions. The salt VBH(+)[H(3)BNH(2)BH(2)NH(2)BH(3)](-) (1) containing a linear … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
74
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(85 citation statements)
references
References 27 publications
10
74
0
1
Order By: Relevance
“…It belongs to the monoclinic Pn space group (Table S1w). All N-B bond distances and bond angles are comparable with those observed in the gauche form and other reported B-N chain anion compounds, [14][15][16][17] and fall within the normal range (Table S2w). The striking feature of the molecular structure is that DDAB adopts an anti, rather than gauche, conformation (Fig.…”
Section: 2supporting
confidence: 85%
See 1 more Smart Citation
“…It belongs to the monoclinic Pn space group (Table S1w). All N-B bond distances and bond angles are comparable with those observed in the gauche form and other reported B-N chain anion compounds, [14][15][16][17] and fall within the normal range (Table S2w). The striking feature of the molecular structure is that DDAB adopts an anti, rather than gauche, conformation (Fig.…”
Section: 2supporting
confidence: 85%
“…17 In the structure of the anion V, a BH 3 NH 2 BH 2 NH 2 moiety adopts the anti conformation at one end of the anion and the gauche conformation at the other end. In the structure of the anion VI, the BH 3 NH 2 BH 2 NH 2 moiety at both ends adopts the gauche form but the NH 2 BH 2 NH 2 BH 2 moiety at the center adopts the anti form.…”
Section: 2mentioning
confidence: 99%
“…Under the same melt conditions, Fe 2 (CO) 9 was also found to catalyse the dehydrocoupling of H 3 B · PPh 2 H to form the same product (80% conversion in 15 h). The authors postulated that the loss of a carbonyl ligand at high temperatures allowed dehydrocoupling to occur in the vacant coordination site created [172].…”
Section: Group 8 Metal-catalysed Dehydrocoupling Of Phosphine-boranesmentioning
confidence: 84%
“…It is the control of these processes, to either afford well-defined final products or the maximum rate and yield of hydrogen evolution, that makes catalytic routes attractive for dehydrocoupling. This is not the first time that dehydrocoupling of amine-boranes and phosphine-boranes has been reviewed, and there have been recent overviews dealing with their general chemistry and properties [1,2], role in hydrogen storage applications [4,8,9], as well as dehydrocoupling processes [5,7,10,11]. We do not attempt to review the extensive literature on the catalysed hydrolysis of amine-boranes to produce H 2 as the principal product of interest [3].…”
Section: Introductionmentioning
confidence: 99%
“…[1] Light, safe, and compact storage of hydrogen for onboard applications remains the largest challenge in its implementation. [6] Nevertheless, poor recyclability, slow kinetics below 100 8C, and simultaneous liberation of excessive deleterious gases upon thermolysis (i.e., borazine, ammonia, and diborane) [7] are main challenges that need to be addressed before this material can be utilized in practical systems.Initial advances have demonstrated that the promoted rate, extent and purity of H 2 delivery required could be achieved from AB by using a variety of catalytic strategies, such as nanoscaffolds, [8] acids, [9] bases, [10] metal catalysts, [11] among others. [3] Ammonia borane (NH 3 BH 3 , AB) is considered as one of the most promising chemical hydrogen storage materials, [4] attributed to its high material storage density, low thermolysis temperature, [5] and recently realized regenerability.…”
mentioning
confidence: 99%